A Theoretical Study and Analysis of Competitiveness in a Regional Economy - Myskova A. E. (Interactive science, 2020)
the article considers theoretical and practical approaches to determining the competitiveness of a region and the factors that determine it. A general analysis of regional competitiveness indicators has been performed. A study of economic regional development and growth and its connection with the real standard of living of the population of this region is carried out.
Keywords: конкурентоспособность; ресурсы; производство; competitiveness; resources; микроэкономика; production; microeconomics